2021
DOI: 10.1371/journal.pone.0250112
|View full text |Cite
|
Sign up to set email alerts
|

Chinese consumers’ willingness to get a COVID-19 vaccine and willingness to pay for it

Abstract: A COVID-19 vaccine is the key to beating the virus, and effective vaccines are going to be available in the near future. It is urgent to estimate the acceptability of COVID-19 vaccines and their value to individuals, in order to develop an effective public vaccination strategy. Based on a survey of 1,188 randomly selected respondents in China, we analyzed Chinese consumers’ willingness to get a COVID-19 vaccine and their willingness to pay for it. We find that 79.41% of the respondents are willing to get vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 17 publications
(20 reference statements)
2
31
4
Order By: Relevance
“…COVID-19 s novel vaccination technologies, utilizing the messenger RNA and adenoviral transgene delivery, not previously used in the general population, were associated with the generation of many questions that would need answers to help clear the uncertainty among the people [29]. In terms of the cost of the vaccine, the COVID-19 vaccine price being high in the market may deter a substantial share of the at-risk people, especially those earning low incomes, from getting vaccinated against COVID-19 [39]. Furthermore, another study by Gatwood et al suggested that Hispanics, in comparison to Whites and Blacks, had a higher agreement with the statement "New vaccines carry more risks than older vaccines" [32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…COVID-19 s novel vaccination technologies, utilizing the messenger RNA and adenoviral transgene delivery, not previously used in the general population, were associated with the generation of many questions that would need answers to help clear the uncertainty among the people [29]. In terms of the cost of the vaccine, the COVID-19 vaccine price being high in the market may deter a substantial share of the at-risk people, especially those earning low incomes, from getting vaccinated against COVID-19 [39]. Furthermore, another study by Gatwood et al suggested that Hispanics, in comparison to Whites and Blacks, had a higher agreement with the statement "New vaccines carry more risks than older vaccines" [32].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review conducted by Cascini et al found that Arabian countries have shown to have higher reported vaccine hesitancy compared to other nations of the world [48]. Similarly, although China has higher COVID-19 vaccine acceptance rates as opposed to other countries such as France and the US, a study by Qin et al stated that older adults are less willing to receive a COVID-19 vaccine [39]. This high-risk population was also found to not be willing to pay as much for the vaccine, compared to the general population [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the development of COVID-19 vaccines, a number of studies explored consumers’ willingness to pay (WTP) for the COVID-19 vaccine in different countries (see Cerda and García, 2021 ; Dias-Godói et al, 2021 ; García and Cerda, 2020 ; Harapan et al, 2020 ; Muqattash et al, 2020 ; Qin et al, 2021 ; Sarasty et al, 2020 ; Vo et al, 2021 ; Wang et al, 2021 ; Wong et al, 2020 ). As will be discussed in Section 2 , these studies generally found that different consumers have different WTP, which in turn depends on a number of factors, such as income.…”
Section: Introductionmentioning
confidence: 99%
“…Filling this gap, this study takes one step further to estimate demand functions for a COVID-19 vaccine in China and the United Arab Emirates (UAE) and compute the associated consumer surplus, utilizing the WTP data made available by Qin et al (2021) and Muqattash et al (2020) . For this purpose, we first establish an analytical framework, under three weak behavioural assumptions which can be relaxed if one wishes.…”
Section: Introductionmentioning
confidence: 99%